Invertebrate communities, sediment parameters and food availability of intertidal soft-sediment ecosystems on the north coast of British Columbia, Canada. Issue 15 (17th April 2020) - Campbell, Lily; Dudas, Sarah E.; Juanes, Francis; Allen Gerwing, Alyssa M.; Gerwing, Travis G.
ABSTRACT: The Skeena River estuary supports commercial and culturally important salmon fisheries. However, considerable development has occurred in the area, and more has been proposed. If anthropogenic development degrades this critical habitat, the Skeena salmon run, that every year contributes 110 million to local economies, may be negatively impacted. Benthic invertebrates are common indicator species, as they often respond to disturbances before commercial species, warning of potential impacts. Unfortunately, invertebrates in the Skeena estuary have not been extensively studied, and we lack the detailed understanding of their community structure and dynamics for them to serve as indicator species in this region. Therefore, present conditions of the Skeena estuary are established here (invertebrate community, sediment conditions and food availability), in order to provide the data required both to anticipate changes associated with potential anthropogenic disturbances and to detect changes in this system if development occurs.